Australia : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2006)
The report provides a summary of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) measures in place in Australia. It describes and analyzes those measures, and provides recommendations on how certain aspects of the system could be strengthened. Under the Financial Transactions Reports (FTR) Act 1988, cash dealers submit a range of financial transaction reports to AUSTRAC, including reports on suspicious transactions (SUSTRs) and international fund transfers. Australia's legislative framework does not distinguish between financial institutions or specify AML/CFT obligations for financial institutions on the basis of risk. The FTR Act also applies outside Australia.